Sentiment analysis in twitter: Impact of morphological characteristics (2020)
This paper presents a series of experiments aimed at the sentiment analysis on texts posted in Twitter. In particular, several morphological characteristics are studied for the representation of texts in order to determine those that provide the best performance when detecting the emotional charge contained in the Tweets.